Secrecy performance of massive MIMO relay‐aided downlink with multiuser transmission. Issue 9 (1st June 2019) - Nguyen, Do Dung; Bao, Vo Nguyen Quoc; Chen, Qingchun
Abstract : In this study, the authors study secure multiuser transmission in a massive multiple‐input multiple‐output (MIMO) relaying system, where a base station sends its messages to multiusers via an amplify‐and‐forward relay station. Beamforming matrices of maximum ratio combining/maximum ratio transmission (MRC/MRT) and zero‐forcing reception/zero‐forcing transmission (ZFR/ZFT) at relay are considered. The authors derive exact and asymptotic expressions for user rate and outage secrecy rate for a predetermined secure outage probability of eavesdropper links with channel state information imperfection. They have shown that ZFR/ZFT is a better choice than MRC/MRT from the perspectives of secrecy performance. Furthermore, the asymptotic analysis is proposed to show that almost the eavesdropper rates in all cases are degraded as a number of relay antennas goes to infinity, and simultaneously the transmit power at the base station and the relay can be scaled down significantly. Finally, numerical results provide more insightful validity of the proposed analysis.